(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
Health professional education (HPE) has taken a problem-based approach to community service-learning with good intentions to sensitize future health care professionals to community needs and serve the underserved. However, a growing emphasis on social responsibility and accountability has educators rethinking community engagement. Many institutions now seek to improve community participation in educational programs. Likewise, many Canadians are enthusiastic about their health care system and patients, who are “experts by lived experience,” value opportunities to “give back” and improve health care by taking an active role in the education of health professionals. We describe a community-based participatory action research project to develop a mechanism for community engagement in HPE at the University of British Columbia (UBC). In-depth interviews and a community dialogue with leaders from 18 community-based organizations working with vulnerable populations revealed the shared common interest of the community and university in the education of health professionals. Patients and community organizations have a range of expertise that can help to prepare health practitioners to work in partnership with patients, communities, and other professionals. Recommendations are presented to enhance the inclusion of community expertise in HPE by changing the way the community and university engage with each other.